2016
DOI: 10.1016/j.phrs.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide donors alleviate itch secondary to the activation of type-2 protease activated receptors (PAR-2) in mice

Abstract: Hydrogen sulfide (HS) has been highlighted as an endogenous signaling molecule and we have previously found that it can inhibit histamine-mediated itching. Pruritus is the most common symptom of cutaneous diseases and anti-histamines are the usual treatment; however, anti-histamine-resistant pruritus is common in some clinical settings. In this way, the involvement of mediators other than histamine in the context of pruritus requires new therapeutic targets. Considering that the activation of proteinase-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
2
16
0
2
Order By: Relevance
“…When histamine‐independent pruritus was induced by the activation of PAR2 with the peptide agonist SLIGRL‐NH 2 , the response was effectively reduced by NaHS, via ATP‐sensitive potassium channel opening and involving the participation of NO (in a cGMP‐independent manner). Furthermore, in this model, TRPA1 cation channels mediate the PAR2‐induced pruritus, but H 2 S does not interfere with this pathway (Coavoy‐Sánchez et al, 2016).…”
Section: H2s and Skin Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…When histamine‐independent pruritus was induced by the activation of PAR2 with the peptide agonist SLIGRL‐NH 2 , the response was effectively reduced by NaHS, via ATP‐sensitive potassium channel opening and involving the participation of NO (in a cGMP‐independent manner). Furthermore, in this model, TRPA1 cation channels mediate the PAR2‐induced pruritus, but H 2 S does not interfere with this pathway (Coavoy‐Sánchez et al, 2016).…”
Section: H2s and Skin Diseasesmentioning
confidence: 98%
“…We have previously shown that inhibition of endogenous H 2 S synthesis with β‐cyano‐ l ‐alanine (a CSE/CBS inhibitor) results in significant potentiation of the scratching behavior induced by compound 48/80 in mice, along with increased neutrophil recruitment, as measured by myeloperoxidase activity (Rodrigues et al, 2017). Moreover, H 2 S donors can have important therapeutic applications for treatment of both histaminergic and non‐histaminergic pruritus in mice (Coavoy‐Sánchez et al, 2016; Rodrigues et al, 2017). Regarding the histaminergic pathway, the H 2 S donors sodium sulfide (Na 2 S) and Lawesson's reagent (Figure 1) significantly reduced the pruritus induced in mice by the intradermal injection of either histamine or the mast cell degranulator compound 48/80, and these effects were, at least in part, mediated by stabilization of mast cells (Rodrigues et al, 2017).…”
Section: H2s and Skin Diseasesmentioning
confidence: 99%
“…Protein expression of the H 2 S producing enzymes (CSE, CBS, and MPST) in mouse mesenteric artery homogenates was analyzed by Western blotting as previously described [ 32 ]. Briefly, 10 µg of total proteins from homogenates were separated by 10% SDS-PAGE electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“… Inflammatory cutaneous disease Protective role of H 2 S Psoriasis H 2 S level in psoriasis patients are significantly lower than those of healthy controls [155] ; H 2 S inhibits keratinocytes growth, adhesion and IL-8 expression through inhibiting mitogen-activated protein kinase(MAPK) signaling [156] , [157] ; H 2 S donors NaHS and GYY4137 significantly enhance iNOS, resulting in the increase of NO, which down-regulates ERK1/2 activation [158] . Itching-related inflammatory diseases H 2 S donors GYY4137and NaHS significantly reduce pruritus secondary to type-2 protease activated receptors (PAR-2) activation in mice [161] . Chronic skin ulcers or wounds H 2 S accelerates wound healing via inhibiting ROS production, ERK1/2 and p38 activation and enhancing VEGF expression [163] , [164] .…”
Section: Implications Of Endogenous Gasotransmitters Prodrugs and Inh...mentioning
confidence: 99%
“…In addition, Coavoy-Sánchez SA et al indicate that both H 2 S donors GYY4137 and NaHS significantly reduce pruritus secondary to type-2 protease activated receptors (PAR-2) activation in mice [161] . Since pruritus or itching is an unpleasant sensation relevant to disorders of the skin and other organs [162] , H 2 S donors may be promising candidates to treat itching-related inflammatory diseases.…”
Section: Implications Of Endogenous Gasotransmitters Prodrugs and Inh...mentioning
confidence: 99%